(untitled) (Circe de clásicos y modernos, 2018)
This article aims to read Lucillius ́s epigram from the standpoint of the tradition of Greek sympotic poetry. It focuses specifically on the construction of the poet ́s image as the ‘I’ is understood to be the fictionalization of Lucillius himself. It examines the ways in which the author separates himself from the traditional image of the poet in the symposium, while he adopts a marginal and controversial –but still symposiac– figure as the buffoon or parasite. With this, Lucillius reveals the true relationships which regulate the convivial praxis of his time.